The Lessons Will Be Televised: Examining Television Portrayals of Sexual Consequences by Gender. (March 2023) - Stevens Aubrey, Jennifer; Miller, Brandon; Bond, Bradley J.; Roberts, Lindsay
This study examined the sexual double standard in the portrayal of sexual consequences on television. A content analysis of television programs nominated for Teen Choice Awards from 2012 to 2015 revealed that female characters received more negative sexual consequences than male characters, but there was no gender difference in who received positive sexual consequences. The gendered distribution of negative sexual consequences was qualified by age of the casts in the television programs. Negative sexual consequences were significantly more likely to be experienced by female characters than male characters within shows that primarily featured teens, thus reinforcing a discourse of sexual risk and danger for teen girls.